Correlation between Corona Viruses Disease (Covid-19) and C-Reactive Protein (CRP) in Patients at Haji Hospital Surabaya: Hubungan Corona Viruses Disease (Covid- 19) Dan C-Reactive Protein (CRP) Pada Pasien Di Rumah Sakit Umum Haji Surabaya - Saputro , Tri Ade; Purwaningsih, Nur Vita; Ainutajriani, Ainutajriani; Watoyani , Tony (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
Coronavirus Disease (Covid-19) is a new type of virus that has never been previously identified in humans. Common signs and symptoms of Covid-19 infection include symptoms of acute respiratory distress such as fever, cough and shortness of breath. C-Reactive Protein (CRP) is a protein in serum that causes inflammation in the body. The presence of this inflammatory response causes the levels of CRP in the body to increase significantly. To determine the severity of Covid-19 disease, one of the screening tests used is the CRP examination, starting when clinical symptoms appear, becoming high levels of CRP indicating inflammation or inflammation. This study aims to determine CRP levels in patients who were confirmed positive for Covid-19 at RSU Haji Surabaya. The research method used is descriptive research with secondary data. The sample in the study was 60 patients who had confirmed Covid-19 and performed a CRP test from February to June 2021. The sampling technique used a total sampling technique at the Haji General Hospital Surabaya. The results showed that from 60 confirmed Covid-19 inpatients, 58 patients (96.6%) had CRP levels with high risk criteria or CRP levels > 5 mg/L and 2 patients (3.4%) had CRP levels. with normal criteria or CRP levels < 5 mg/L. Based on the results, it can be concluded that CRP levels are positively correlated with the development and severity of Covid-19 disease.